2019
DOI: 10.1177/1120672119848961
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal aflibercept efficacy in neovascular age-related macular degeneration with suboptimal response to anti-vascular endothelial growth factor-A therapy

Abstract: Importance: To provide new insights into aflibercept effect in non-naive-treated patients with neovascular age-related macular degeneration. Purpose: To assess the efficacy of intravitreal aflibercept in patients with neovascular age-related macular degeneration without optimal response to previous anti-vascular endothelial growth factor A therapy. Design: Single-arm, multi-centre, prospective study. Participants: Patients ⩾50 years with active neovascular age-related macular degeneration, best-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Finally, this study found that the incidence of adverse reactions in the observation group was lower than that in the control group, suggesting that intravitreal injection of aflibercept in the treatment of DR cystoid macular edema is safe, which is consistent with what Monés et al [ 20 ] has proposed. However, the average number of injections in the observation group was higher than that in the control group.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, this study found that the incidence of adverse reactions in the observation group was lower than that in the control group, suggesting that intravitreal injection of aflibercept in the treatment of DR cystoid macular edema is safe, which is consistent with what Monés et al [ 20 ] has proposed. However, the average number of injections in the observation group was higher than that in the control group.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this, several studies of eyes with nAMD have shown that switching to aflibercept 2 mg can improve visual and anatomic outcomes, although in some cases also allowing for extension of the dosing interval in eyes with a suboptimal response to ranibizumab or bevacizumab. 3336 In a small study, aflibercept HD was effective in 38 eyes (33 patients) with nAMD that did not respond to standard doses of ranibizumab or bevacizumab. 10…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, several studies of eyes with nAMD have shown that switching to aflibercept 2 mg can improve visual and anatomic outcomes, although in some cases also allowing for extension of the dosing interval in eyes with a suboptimal response to ranibizumab or bevacizumab. [33][34][35][36] In a small study, aflibercept HD was effective in 38 eyes (33 patients) with nAMD that did not respond to standard doses of ranibizumab or bevacizumab. 10 The present analysis extends these findings by showing the potential benefits of aflibercept HD therapy in eyes resistant to anti-VEGF agents with a broader range of indications for intensifying treatment for a cohort that is larger than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…78 In a prospective, single arm, multi-centre study with 46 nAMD patients undergoing aflibercept treatment for 3 months, 45.7% (95% CI, 31.5%-60.1%) presented no IRF or SRF on OCT imaging at week 12, and a clinically significant improvement was found for BCVA [mean (SD); +4.5 (5.8) P < 0.0001]. 97 In the retrospective study of patients with AMD switched from ranibizumab to aflibercept treatment, there was almost perfect agreement 98 between raters for identifying presence of IRF on SD-OCT exams (Kappa statistic of 0.859) and substantial agreement 98 between raters for SRF (Kappa statistic of 0.713). 23 Another study 99 using a sample of 270 TD-OCT exams from the CATT found good agreement 98 between reading teams (with each team composed of 2 certified readers and one senior reader to reconcile discrepancies) at a reading centre for identifying presence of IRF (Kappa statistic of 0.48) and substantial agreement for identifying presence of SRF (Kappa statistic of 0.80).…”
Section: Presence Of Intraretinal Fluid And/or Subretinal Fluid and P...mentioning
confidence: 99%